"Vom Polocker Venedig" Kollektives Handeln sozialer Gruppen einer Stadt zwischen Ost- und Mitteleuropa (Mittelalter, frühe Neuzeit, 19. Jh. bis 1914) - Rohdewald, Stefan (Franz Steiner Verlag, 2005)
So far, there are hardly any studies that examine the history of a single city of the eastern Slavic settlement area over a longer period. The example of Polock shows how a significant Rus' princely seat in contact with East Central Europe changed profoundly from the thirteenth century. In the context of Poland-Lithuania, conflict-ridden religious formation processes and the emergence of orthodox and uniate guilds and lay brotherhoods in the 17th century were followed by late-antiquity commune-taking in the late Middle Ages. The legal inconsistency of the city made it the sanctuary of a growing Jewish community. After the integration into the Tsarist empire in 1772, the Jews were integrated into the municipal self-government, but in 1892 excluded from it.
Description based on print version record.
KU Open Services
Keywords: History / Europe / Eastern; History; Electronic books